Impact of the Digital Sales Growth Of MSMEs Industry Fashion in Bandung City: Product Recommendations, Customized Promotions, Customer Reviews, and Product Ratings - Frans Sudirjo; Ari Apriani; Arief Yanto Rukmana; Djoko Widagdo; Egidius Fkun (Jurnal Bisnisman : Riset Bisnis dan Manajemen, 2023)
This study aims to examine the impact of digital sales growth on the fashion industry of micro, small, and medium enterprises (UMKM) in the city of Bandung, particularly in terms of product recommendations, personalized promotions, customer reviews, and product ratings. A quantitative research approach was employed, and data were collected through an online survey distributed to fashion UMKM practitioners in Bandung. The findings indicate that digital sales growth has a significant impact on the fashion industry of UMKM in Bandung by enhancing business visibility and accessibility to potential customers, facilitating the creation of personalized marketing strategies, and providing a platform for customer interaction and feedback. The study suggests that fashion UMKM practitioners should invest in digital marketing tools and strategies to remain competitive and adapt to changes in consumer behavior in the digital era.